APRESENTAÇÃO - Kress, Tricia; Amorim, Simone (Interfaces Científicas - Educação, 2018)
Critical Pedagogy and Educational ResearchScholar‐practitioners of critical pedagogy and critical research on and extend a number of theories and methods but have the common goal of giving education and research a humanized approach in contemporary society, through Critical Pedagogy. This special issue aims at providing a broad overview of why researchers embrace critical pedagogy and critical research. Inspired by critical theory and other philosophies, Critical Pedagogy seeks to develop awareness and help question beliefs and practices that are alleged to dominate.